ANALISIS BULLWHIP EFFECT PADA PERENCANAAN KEBUTUHAN MATERIAL BELT CONVEYOR - febryanto, indra (LPPM Universitas PGRI Adi Buana Surabaya, 2018)
Controlling the supply of raw materials belt conveyor is a very important management function because it is a vital company investment, both in terms of value and future prospects. Well-implemented inventory control management can trigger a company's success in production. In manufacturing companies there is often a delay in the arrival of material arrival due to various things, such as the bullwhip effect between the company with suppliers, companies with distributors or companies with buyers. The focus of this research is to know how big the occurrence of bullwhip effect and how to decrease the bullwhip effect that already happened. From the calculation results obtained a decrease in the value of the bullwhip effect from the original to PU White products 2,786 to 1,524, blue PU products 3,297 to 1,455, and PVC Green 2.025 to 1.5794.